Perancangan Knowledge Management System pada Bagian Diklat PT Dirgantara Indonesia - Joeliaty Joeliaty; Ajeng Pritha Aryani (Jurnal Manajemen dan Bisnis Indonesia, 2014)
The problem that emerged on every organization now days especially company is how to increase sustainable knowledge from their human resources that suitable with the challenges faced. However, a lot of organizations such as PT Dirgantara Indonesia is not yet or have not discovered hidden knowledge within their employees. Therefore, the objective of this research is to find a constructive plan, implementation and evaluation of Knowledge Management System (KMS) that should be applied to PT Dirgantara Indonesia. Research method used on this paper is descriptive qualitative methodology, 10-step knowledge management roadmap, and differentiation quantitative test. The results from this research are implementations on business startegy of PT Dirgantara Indonesia on their Training and Education Department, with personal approach. Knowledge that needs to be followed is career analysis method, English language ability, SAP creation and system analysis. Those implementations are running through online forum such as intranet portal and offline forum such as scheduled formal forum. Keywords : knowledge management strategy, knowledge management system, 10 steps roadmap, SECI model, MOODLE